Mbangu eka tsalwa ra i vutomi hi C.M. Lubisi na ra xona hi xihi? hi D.R. Maluleke - Shirelele, T. I. (University of Limpopo, 2011)
This study is to conduct a detailed study of milieu in a number of Xitsonga novels in I Vutomi by Lubis CM and Xona hi Xihi? by DR Maluleke. This study also emphasizes on how the characters are depicted in rural areas and urban places. Lubisi and Maluleke are able to enlighten the community about the importance of establishing the distinct relationship between space and time. The first chapter is a general introduction that outlines and provides background of the study. Milieu as well as its manifestation in I Vutomi and Xona hi Xihi? is discussed in the second chapter. The third chapter deals with characterization. In the fourth chapter, the main theme of the novels is critically examined. The fifth chapter is a brief overview of the first four chapters. It also summarizes the findings of the research and provides recommendations.
Thesis (M.A.) --University of Limpopo, 2011
Keywords: Millieu; Tsonga novels; Distinct relationship between space and time; Milieu therapy; Therapeutic communities